Imaging of Common Spinal Cord Diseases - Russo, Camilla; Muto, Gianluca; Giordano, Flavio; Masala, Salvatore; Muto, Mario (Seminars in Musculoskeletal Radiology, 2022)
Spinal cord evaluation is an integral part of spine assessment, and its reliable imaging work-up is mandatory because even localized lesions may produce serious effects with potentially irreversible sequelae. Spinal cord alterations are found both incidentally during spine evaluation in otherwise neurologically asymptomatic patients or during neurologic/neuroradiologic assessment in myelopathic patients. Myelopathy (an umbrella term for any neurologic deficit that refers to spinal cord impairment) can be caused by intrinsic lesions or extrinsic mechanical compression, and its etiology may be both traumatic and/or nontraumatic. The symptoms largely depend on the size/extension of lesions, ranging from incontinence to ataxia, from spasticity to hyperreflexia, from numbness to weakness. Magnetic resonance imaging is the reference imaging modality in spinal cord evaluation, ensuring the best signal and spatial resolution. We provide an overview of the most common spinal cord disorders encountered by radiologists and describe the technical measures that offer optimal spinal cord visualization.
Keywords: central nervous system; spine; spinal cord; myelopathy; magnetic resonance imaging